The Impact Of Yoga And Mindfulness On Well-Being Of School Students In New Zealand – Applying The Principles of Te Whare Tapa Whā Model - Fraser, Victoria; Laxman, Kumar (International Research Journal of Ayurveda & Yoga, 2021)
This study conducted in a school in New Zealand examined the impact of a yoga program on the well-being of school students. The aim of the study was to explore if yoga could be utilized as a tool to enhance overall well-being as explained in the Te Whare Tapa Whā model. A mixed methods research design was adopted in the design and implementation of this study. Overall, findings of this research have been optimistic with students acknowledging positive changes within themselves physically, mentally and emotionally with additional enhanced self-awareness.